Quality metrics for mutation testing with applications to WS‐BPEL compositions. (10th May 2014) - Estero‐Botaro, Antonia; Palomo‐Lozano, Francisco; Medina‐Bulo, Inmaculada; Domínguez‐Jiménez, Juan José; García‐Domínguez, Antonio
Summary: Mutation testing is a successful testing technique based on fault injection. However, it can be very costly, and several cost‐reduction techniques for reducing the number of mutants have been proposed in the literature. Cost reduction can be aided by an analysis of mutation operators, but this requires the definition of specialized metrics. Several metrics have been proposed before, although their effectiveness and relative merits are not easy to assess. A step ahead in the evaluation of mutation‐reduction techniques would be a better metric to determine objectively the quality of a set of mutants with respect to a given test suite. This work introduces such a metric, which is naturally extended to mutation operators and may be used to reduce the number of mutants, particularly of equivalent mutants. Finally, a firm mutation analysis tool for WS‐BPEL service compositions is presented, and experimental results obtained by comparing different metrics on several compositions are presented. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Mutation testing is a successful testing technique. However, it can be very costly. Cost reduction can be aided by an analysis of mutation operators, but this requires the definition of specialized metrics. A better quality metric for mutants would be a first step towards improved cost reduction techniques. This work introduces such a metric and a firm mutation tool for WS‐BPEL compositions. Experimental results obtained by comparing different metrics on several compositions are presented. Copyright © 2014 John Wiley & Sons, Ltd.